Lawatan Misi Kesenian Mangkunegaran ke Mancanegara 1989: Kontribusi bagi Pembangunan Nasional - Meilinia Fathonah; Dhanang Respati Puguh (Department of History, Faculty of Humanities, Diponegoro University, 2022)
This study argues the Mangkunegaran Arts Mission Visit to foreign countries in 1989 as an effort to contribute to Indonesia's national development. The mission which held in 1989, exactly a year after K.G.P.H. Djiwokusumo was inaugurated as the head of the Mangkunegaran Temple with the title K.G.P.A. Mangkunegara IX. The countries which had been visited on the tips were France, Britain and Japan which had become the member of Group of Seven (G-7) and had a large share in determining international economic policy. The decline in the country's foreign exchange in 1986 due to the devaluation of Rupiah against the dollar as well as on the declined of oil and gas prices spurred the New Order government to promote tourism as an alternative solution. The visit of the Mangkunegaran Arts Mission to foreign countries has become one of the promotional media for Indonesian tourism to attract foreign tourists. This momentum can not be separated from the great mission of Mangkunegara VIII and the pre-eminent oath of Mangkunegara IX to develop Mangkunegaran as a center of Javanese culture. Through historical methods, this study reveals the reasons and process of the implementation of Mangkunegaran Arts Mission Visit and explores the meaning of the visit for Indonesia's national development during the New Order Period. Because it moves from the momentum of an arts mission tour, this study can be used as a basis for policy making in the future.